Image quality optimization of dental panoramic tomogram and lateral cephalogram: a pilot study on human skull / Liyana Ghazali, Mohd Yusmiaidil Putera Mohd Yusof and Noraina Hafizan Norman - Ghazali, Liyana; Mohd Yusof, Mohd Yusmiaidil Putera; Norman, Noraina Hafizan (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
Purpose: The purpose of this study was to investigate the effects of varying scanning parameters of DPT and LC on diagnostic performance and quality of the images. Materials and Methods: Clinical evaluations of image quality were performed using an adult human skull with permanent dentition. Dental panoramic tomogram (DPT) and lateral cephalogram (LC) images were obtained using two different radiographic machines Instrumentarium 300OP taken at Sungai Buloh (SB) and Sirona Orthophos 3D taken at Puncak Perdana (PP) by varying tube voltages. Two orthodontic residents assessed images based on overall quality using a five-point rating scale and diagnostic performance by detection of anatomical landmarks. The correlations between radiation doses and diagnostic value of the images were analyzed using Pearson's Correlation Test. Univariate analysis was calculated for the evaluation for image quality. Intra-class Correlation Coefficient (ICC) was used to test for intra-rater and inter-rater reliability. Results: Both modalities taken at both centers showed negative correlation between dosage and detection of anatomical landmarks except for LC SB. All images were rated at least with median of 3= more than adequately presented regardless of the radiation dosage except for DPT PP (median 5= inadequately presented). Conclusion: Lower dosage parameters should be used when taking DPT and LC as images appeared darker, lower in quality and less anatomical landmarks can be detected at higher scanning parameter.